The temporal dynamics of terrestrial organic matter transfer to the oceans : initial assessment and application - Drenzek, Nicholas J (Massachusetts Institute of Technology, 2007)
Thesis (Ph. D.)--Joint Program in Oceanography/Applied Ocean Science and Engineering (Massachusetts Institute of Technology, Dept. of Earth, Atmospheric, and Planetary Sciences; and the Woods Hole Oceanographic Institution), 2007. Includes bibliographical references. This thesis employs compound-specific stable carbon and radiocarbon isotopic analysis of organic biomarkers to (a) resolve petrogenic from pre-aged vascular plant organic carbon (OC) in continental margin sediments, (b) investigate the underlying mechanisms controlling the anomalously old ages that are often observed for the terrestrial component of sedimentary OC, and (c) address the associated consequences for biomarker-based climate reconstructions. In Chapters 2 and 3, coupled molecular isotope mass balances demonstrate that the amount of petrogenic OC residing on the Beaufort Shelf (Arctic Ocean) and the Eel River Margin (coastal California) has been previously overestimated due to the presence of significantly 'pre-aged' terrestrial OC. However, even though the contribution of organic matter emanating from sedimentary rocks may be smaller, these results reinforce the emerging notion that it is not completely oxidized during weathering and subsequent seaward transport. In Chapter 4, comparison of the down-core radiocarbon profiles for certain vascular plant biomarkers extracted from Cariaco Basin (Caribbean Sea) and Saanich Inlet (coastal British Columbia) sediments with the radiocarbon evolution of atmospheric carbon dioxide reveals that the vast majority of the terrestrial OC experiences multi-millennial residence times on land prior to entering the sea. Most of the remaining inventory is deposited in sediments within one or two decades, providing direct evidence that very little terrestrial organic matter is rapidly transferred to the marine environment. (cont.) With this in mind, the striking modulation in the signal amplitude of a biomarker-based tropical paleoaridity record presented in Chapter 5 was instead used to evaluate the ...